2020
DOI: 10.3390/app10165506
|View full text |Cite
|
Sign up to set email alerts
|

Cost Overrun Causative Factors in Road Infrastructure Projects: A Frequency and Importance Analysis

Abstract: Road infrastructure projects are essential for a country’s economic and social development. Due to the magnitude, the projects are associated with considerable economic investments that in the case of failure can seriously affect regions’ economies. Despite the importance, roads from different countries are affected by cost overruns, hence, it is essential to identify and analyze the causative factors to focus the search for mitigation solutions. There are several studies focused on the cost factors identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 80 publications
0
35
0
3
Order By: Relevance
“…He found that publicly funded highway projects are significantly affected by the political uncertainty and its influence on ongoing key projects. Furthermore, Herrera et al (2020), revealed that the political situation in most countries, particularly, developing countries due to government changes can create favourable environment for cost overrun occurrence and eventually compromise the successful project development. As emphasised by some of the interviewees:…”
Section: 22mentioning
confidence: 99%
“…He found that publicly funded highway projects are significantly affected by the political uncertainty and its influence on ongoing key projects. Furthermore, Herrera et al (2020), revealed that the political situation in most countries, particularly, developing countries due to government changes can create favourable environment for cost overrun occurrence and eventually compromise the successful project development. As emphasised by some of the interviewees:…”
Section: 22mentioning
confidence: 99%
“…This study uses two types of approaches in the process of statistical analysis for data collection and processing. The two approaches taken are a kind of quantitative approach and a qualitative approach [19][20][21]. For the two types of approaches used, there are some differences in the methods and techniques used, such as objectives, concepts, research approaches, data collection methods, data analysis, and sampling [21][22].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, shortage of material, lack of plant and spare parts of equipment, acceleration required by clients, change of work scope or changes in material specification by clients, mistakes during construction, fluctuation in prices of raw materials, shortage of workforce, lack of skilled labour, poor project management, poor cost control and awarding of a contract to the lowest bidders were reported as the critical factors. In addition, Herrera et al (2020) identified failures in design, price variation of materials, inadequate project planning, project scope changes and design changes as contributing factors.…”
Section: Cost Factorsmentioning
confidence: 99%